Nonliteral Language in Polish Children’s Literature: Cognitive and Linguistic Implications - Siemieniuk, Aleksandra; Taczkowska, Kalina; Banasik-Jemielniak, Natalia (International Journal of Language and Literary Studies, 2025)
This article explores the role of children’s literature as a significant source for understanding nonliteral language comprehension among Polish-speaking children in Poland. It highlights how books, including comics and graphic novels, expose young readers to figurative expressions and facilitate inference-making, essential for grasping the intentions and emotions conveyed in narratives. Despite the well-documented benefits of early exposure to nonliteral language, research exploring its prevalence and types in children’s literature remains limited. This study investigates the implications of nonliteral language for cognitive development and social interaction, addressing the conflicting attitudes that parents and caregivers hold toward its use. Furthermore, it examines the inconsistencies in existing literature regarding the age at which children begin to understand nonliteral forms of communication, such as irony and sarcasm. Focusing on children’s literature as a critical factor in language acquisition, this article aims to provide insights into the developmental pathways through which children learn to navigate the complexities of figurative language, ultimately contributing to ongoing discussions in media studies concerning children’s interactions with text.